How Do You Like Me Now?: Exploring Subjectivities and Home/Field Boundaries in Research with Women in Sex Work - Dewey, Susan; Orchard, Treena (Anthropologica, 2017)
Anthropological analyses of blurred researcher–participant relationships and fieldwork boundaries in settings that double as the field and the researcher’s home typically focus on the anthropologist’s experiences, to the exclusion of how participants construct their own subjectivities in these fluid field sites. Using ethnographic vignettes from our research with women in sex work conducted in the neighbourhoods and services provision sites where we live and work, this article introduces the concept of “subjectivity work” as a means of exploring how we, alongside our participants, reconfigured our relationships to each other and the shifting boundaries of the field.